Mutations in TNFRSF13B encoding TACI are associated with common variable immunodeficiency in humans. - Salzer, U; Chapel, H; Webster, A; Pan-Hammarström, Q; Schmitt-Graeff, A; Schlesier, M; Peter, H; Rockstroh, J; Schneider, P; Schäffer, A; Hammarström, L; Grimbacher, B (2005)
The functional interaction of BAFF and APRIL with TNF receptor superfamily members BAFFR, TACI and BCMA is crucial for development and maintenance of humoral immunity in mice and humans. Using a candidate gene approach, we identified homozygous and heterozygous mutations in TNFRSF13B, encoding TACI, in 13 individuals with common variable immunodeficiency. Homozygosity with respect to mutations causing the amino acid substitutions S144X and C104R abrogated APRIL binding and resulted in loss of TACI function, as evidenced by impaired proliferative response to IgM-APRIL costimulation and defective class switch recombination induced by IL-10 and APRIL or BAFF. Family members heterozygous with respect to the C104R mutation and individuals with sporadic common variable immunodeficiency who were heterozygous with respect to the amino acid substitutions A181E, S194X and R202H had humoral immunodeficiency. Although signs of autoimmunity and lymphoproliferation are evident, the human phenotype differs from that of the Tnfrsf13b-/- mouse model.